THE EFFECT OF FINANCIAL LITERACY, LIFESTYLE, AND SOCIAL MEDIA INTERACTION ON DOOM SPENDING BEHAVIOUR WITH FOMO AS MEDIATOR - Hawa Zahrani; Husaini; Ghazali Syamni; Chairil Akhyar; Nurhasanah (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyse the influence of financial literacy, lifestyle, and social media interaction on doom spending behaviour, with Fear of Missing Out (FOMO) as a mediating variable, among students in the Faculty of Economics and Business at Universitas Malikussaleh. Excessive, anxiety-driven spending has become increasingly common among the younger generation as they navigate economic uncertainty and pervasive digital exposure, making it important to understand which psychological, social, and financial factors drive this behaviour among university students. A quantitative research design was employed using a survey method distributed to active university students selected through purposive and proportional sampling. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with a sample of 140 respondents. The findings reveal that financial literacy, social media interaction, and FOMO significantly and positively affect doom spending behaviour, whereas lifestyle does not exhibit a significant effect. Furthermore, the mediation analysis indicates that FOMO mediates the relationship between social media interaction and doom spending behaviour, but does not mediate the relationships of financial literacy or lifestyle with doom spending behaviour. These findings confirm that FOMO functions as a key psychological mechanism reinforcing consumptive behaviour among students, and that financial knowledge alone is insufficient to prevent it. The results suggest that initiatives to reduce excessive spending among students should combine financial literacy education with healthier, more mindful social media use and emotional-regulation support.